2020
DOI: 10.21203/rs.3.rs-35537/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nondestructive estimation of potato yield using relative variables derived from multi-period LAI and hyperspectral data based on weighted growth stage

Abstract: Background: The accurate estimation of potato yield at regional scale is crucial for food security, precision agriculture and agricultural sustainable development. Methods: In this study, we developed a new method using multi-period relative vegetation indices (rVIs) and relative leaf area index (rLAI) data to improve the accuracy of potato yield estimation based on the weighted growth stage. Two experiments of field and greenhouse (water and nitrogen fertilizer experiments) in 2018 were performed to obtain th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Most previous research on hyperspectral vegetation parameter estimation has used traditional machine learning methods, such as support vector machine (SVM) and random forest (RF) [26][27][28]. With the development of deep learning techniques, researchers have found that this data-driven approach is suitable for modeling structurally complex or high-dimensional data [29].…”
mentioning
confidence: 99%
“…Most previous research on hyperspectral vegetation parameter estimation has used traditional machine learning methods, such as support vector machine (SVM) and random forest (RF) [26][27][28]. With the development of deep learning techniques, researchers have found that this data-driven approach is suitable for modeling structurally complex or high-dimensional data [29].…”
mentioning
confidence: 99%